Impact of Cocoa Seed Extract Toothpaste on Plaque Reduction in Pediatric Populations - Nuraskin, Cut Aja; Salfiyadi, Teuku; Reca, Reca; Mardiah, Ainun (Grimsa Journal of Science Engineering and Technology, 2024)
Plaque is a soft deposit that forms a helical biofilm layer and attached tightly to the tooth surface, in which its presence requiring the use of specific control agents. The safest and most effective plaque control is to use a toothbrush and toothpaste. On the other hand, extract from Theobroma cacao L. seeds contains antioxidant and antibacterial secondary metabolites which could act as a toothpaste active agent. The aim of this research was to determine the impact of Theobroma cacao L. seeds-added toothpaste in reducing plaque index of among children. This is a non-blinding clinical experiment with a pre-test and post-test research design. The research subjects were 30 healthy children aged 8-10 years which were randomly divided into three arms (treatment and control). The results revealed that Theobroma cacao L. extract used as the active ingredient contained contains phenolics, tannins, flavonoids, terpenoids, saponins, and alkaloids. Significantly higher plaque index reductions were observed among children treated with toothpaste containing 1% (mean difference=2.060; p=0.06) as compared to control. In conclusion, the Theobroma cacao L. seeds-added toothpaste could significantly reduce plaque index among healthy children.